Novel application of the Clavien-Dindo classification system and the comprehensive complications index® in microvascular free tissue transfer to the head and neck. (July 2019) - Ebner, Julian Jakob; Mehra, Tarun; Gander, Thomas; Schumann, Paul; Essig, Harald; Zweifel, Daniel; Rücker, Martin; Slankamenac, Ksenjia; Lanzer, Martin
Highlights: CDC and CCI® facilitatestandardization of complication grading. CDC and CCI®applicability for head & neck microvascular reconstruction established. Furtheradaptations of CDC and CCI® have been suggested. Head & neckrisk factors for morbidity and more severe complications identified.